2010
DOI: 10.1002/jcop.20371
|View full text |Cite
|
Sign up to set email alerts
|

The relation of perceived and received social support to mental health among first responders: a meta‐analytic review

Abstract: There are plenty of theories that may support the protective role of social support in the aftermath of potentially traumatic events. This metaanalytic review examined the role of received and perceived social support in promoting mental health among first responders (e.g., firefighters, police officers, and paramedics or emergency medical services personnel). Results showed that the effect sizes derived from 37 empirical studies ranged from 0 to 0.46. The overall weighted mean effect size was of medium magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
255
2
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(275 citation statements)
references
References 82 publications
12
255
2
6
Order By: Relevance
“…J o u r n a l o f P u b l i c M e n t a l H e a l t h (Pajulo et al, 2001), more symptoms of depression and anxiety following stillbirth (Cacciatore et al, 2009), and greater anxiety in those undergoing treatment for ovarian cancer (Hipkins et al, 2004). A meta-analysis has also found that perceived social support was relatedis linked to mental health in emergency services personnel (Prati & Pietrantoni, 2010).…”
Section: Baseline Correlationsmentioning
confidence: 99%
“…J o u r n a l o f P u b l i c M e n t a l H e a l t h (Pajulo et al, 2001), more symptoms of depression and anxiety following stillbirth (Cacciatore et al, 2009), and greater anxiety in those undergoing treatment for ovarian cancer (Hipkins et al, 2004). A meta-analysis has also found that perceived social support was relatedis linked to mental health in emergency services personnel (Prati & Pietrantoni, 2010).…”
Section: Baseline Correlationsmentioning
confidence: 99%
“…The second level of the socio-interpersonal framework model captures interaction processes in close relationships, such as social support, empathy, and communication factors. Higher perceived social support was shown to be predictive of better mental health among crisis aid workers (Prati & Pietrantoni, 2010), and of less adjustment problems in cancer patients (Rizalar, Ozbas, Akyolcu, & Gungor, 2014). Likewise, the quality of social support resources seems to influence the psychological adjustment outcome after stress exposure (Ajrouch, Abdulrahim, & Antonucci, 2013; Brewin, Andrews, & Valentine, 2000).…”
Section: Socio-interpersonal Model Of Stress-response Syndromesmentioning
confidence: 99%
“…They form part of a group of first responders who serve the immediate needs of community members when traumatic incidents occur. Exposure to such incidents leaves them in physical and mental states of health that require social support from others (Prati & Pietrantoni, 2010).…”
Section: Problem Statementmentioning
confidence: 99%
“…
Whilst there is a relationship between social support and mental health amongst first responders on the assumption that social support mediates stress, one also finds mixed evidence of a strong and insignificant association between the two in critical incidents (Prati & Pietrantoni, 2010). This mixed evidence pertains to the following: Varying theoretical assumptions have been revealed
Orientation:

The extensive role that social support plays in the lives of South African Police Service (SAPS) members outside of the expected work networks of professionals and colleagues should be further studied to reflect on the benefits received when handling the stressful and traumatic effects of operational work.

Research purpose: The objective of this study was to describe the concepts of multifaceted social support network systems as perceived by SAPS members in the context of the Vhembe District (South Africa) in assisting them to deal with the effects of their operational work.

Motivation for the study: There is still a call in social research to focus on the influence of different functions and sources of social support.

Research design, approach and method: A descriptive phenomenological research design was used, and 20 SAPS participants were selected through purposive sampling.

…”
mentioning
confidence: 99%